Empagliflozin-Metformin Combination Has Antioxidative and Anti-Inflammatory Properties that Correlate with Vascular Protection in Adults with Type 1 Diabetes. (17th May 2022) - Janić, Miodrag; Cankar, Matej; Šmid, Jan; France Štiglic, Alenka; Jerin, Aleš; Šabovič, Mišo; Janež, Andrej; Lunder, Mojca
Abstract : Background and Aim . Our previous study showed that the empagliflozin-metformin combination significantly improved arterial function; i.e., it improved endothelial function (measured by flow-mediated dilation and reactive hyperaemia index) and reduced arterial stiffness (measured as pulse wave velocity and local carotid artery stiffness) in adults with type 1 diabetes. In the present study, we explored the underlying mechanism by investigating the antioxidative and anti-inflammatory properties of the empagliflozin-metformin combination (compared to the individual drugs or placebo) and its association with improving arterial function. Methods . 40 individuals with type 1 diabetes (average age of 44.7 ± 2.5 years) were randomized into four groups: (1) control (placebo), (2) empagliflozin 25 mg daily, (3) metformin 2000 mg daily, and (4) empagliflozin-metformin combination (25 mg and 2000 mg daily, respectively). At inclusion and after 12 weeks of treatment, the blood samples were collected, and the oxidative stress (total antioxidative status (TAS), superoxide dismutase (SOD), glutathione peroxidase (GPx), uric acid, advanced oxidation protein products (AOPP), advanced glycosylation end products ((AGE) and isoprostane), and inflammation (C-reactive protein (CRP) and interleukin-6 (IL-6)) parameters were determined. Results . The empagliflozin-metformin combination increased levels of the antioxidants (TAS, SOD, and GPx up to 1.1-fold; P < 0.01 ), decreased the levels of prooxidants (AOPP and isoprostanes up to 1.2-fold, P < 0.01 ; AGE up to 1.5-fold, P < 0.01 ), and decreased inflammatory parameters (up to 1.5-fold, CRP P < 0.01 ; IL-6 P < 0.001 ). Antioxidative action was associated with the improvement in arterial function (obtained in the previous study) in the empagliflozin-metformin combination group. Conclusion . Empagliflozin-metformin combination has strong antioxidative and anti-inflammatory capacity, in adults with type 1 diabetes that is greater than that for the individual drugs. Its antioxidative activity at least partially explains the improvement in arterial function. Therefore, it appears that the combination provides the most powerful vascular protection.